Constructivist Didactics Of Leadership Management In The Covid 19 Pandemic Era To Improve Work Communication In Educational Institution - Zahdi; Sulthan Syahril; Subandi; Ida Umami; Siti Patimah; Koderi (International Journal of Science, Technology & Management, 2021)
World Bank mentioned that the COVID-19 pandemic is threatening and hasgreat potential to make education worse. The pandemic has had a hugeimpact on education by closing schools. However, in overcoming thisdisruption, crises can become opportunities. The first step to successfullyaddressing school closures by protecting health and safety is to preventstudents from losing their learning using distance learning. At the same time,countries need to start planning for school reopening. That meanspreventing dropouts, ensuring healthy school conditions, and using newtechniques to promote rapid learning recovery in key areas once studentsreturn to school. The purpose of this study was to analyze the leadershipmanagement in the COVID-19 pandemic era to improve workplacecommunication. This study used the qualitative case study method. Theinstruments used were observation, interview, and documentation.